Exercise Prescription in Chronic Low Back Pain - GÜNDÜZ, OSMAN HAKAN (BAYCINAR MEDICAL PUBL-BAYCINAR TIBBI YAYINCILIK, 2014)
Chronic low back pain is a health problem that causes serious clinical, social, and economic losses and affects the majority of the world's population. Chronic low back pain is one of the most common causes of disability affecting social life and the work environment. In the treatment of low back pain, there are pharmacological therapy, physical therapy, invasive methods, and exercises. Low back pain that lasts less than 6 weeks is defined as 'acute;' low back pain between 6-12 weeks is 'subacute' and 'chronic' when it is more than 12 weeks. While patient education and being active are recommended in acute low back pain, no specific exercise is recommended in the guidelines. Treatment approaches in subacute and chronic low back pain are similar, too, and in the treatment, specific types of exercises, such as core stabilization exercises and McKenzie exercises, are indicated as effective. No matter what type of exercise is given, its effectiveness depends on the person himself, the treatment, and person's desire to be healthy. The efficacy of exercise could be increased with supervision of exercise, motivation-enhancing behavior therapy, and exercise selection that is suitable with the individual's talents and skills.
Keywords: Low back pain; conservative treatment; exercise; STABILIZATION EXERCISE; THERAPY; GUIDELINES; MANAGEMENT; DISABILITY; EFFICACY; METAANALYSIS; PREVALENCE